2006
DOI: 10.1007/s00441-006-0180-x
|View full text |Cite
|
Sign up to set email alerts
|

Caudal neurosecretory system of the zebrafish: ultrastructural organization and immunocytochemical detection of urotensins

Abstract: The caudal neurosecretory system is described here for the first time in the zebrafish, one of the most important models used to study biological processes. Light- and electron-microscopical approaches have been employed to describe the structural organization of Dahlgren cells and the urophysis, together with the immunohistochemical localization of urotensin I and II (UI and UII) peptides. Two latero-ventral bands of neuronal perikarya in the caudal spinal cord project axons to the urophysis. The largest secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…The axon terminals releasing UII into the urophysis originate from Dahlgren cells, i.e., large cholinergic neurons that are located in the caudal region of the ventral horn of the spinal cord of teleosts (Enami, 1959). Immunohistochemical labeling has confirmed that UII is primarily located in neurosecretory cells of the ventral spinal cord (Owada et al, 1985;Oka et al, 1989;Parmentier et al, 2006). However, subsequent studies have shown that UII is also present in the fish brain (Waugh and Conlon, 1993), and the expression of UII mRNA in fish brain has been confirmed by reverse-transcription polymerase chain reaction (RT-PCR; Lu et al, 2006;Sun et al, 2014).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…The axon terminals releasing UII into the urophysis originate from Dahlgren cells, i.e., large cholinergic neurons that are located in the caudal region of the ventral horn of the spinal cord of teleosts (Enami, 1959). Immunohistochemical labeling has confirmed that UII is primarily located in neurosecretory cells of the ventral spinal cord (Owada et al, 1985;Oka et al, 1989;Parmentier et al, 2006). However, subsequent studies have shown that UII is also present in the fish brain (Waugh and Conlon, 1993), and the expression of UII mRNA in fish brain has been confirmed by reverse-transcription polymerase chain reaction (RT-PCR; Lu et al, 2006;Sun et al, 2014).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…qPCR analysis in 5 control and 5 rpgrip1l ∆/∆ fish at the 3-4 wpf stage (0.8-0.9 cm) confirmed urp2 overexpression in rpgrip1l ∆/∆ fish and showed that this overexpression preceded scoliosis onset ( Figure 4A). To investigate the tissue specificity of this up-regulation, we performed immunofluorescence with an antibody to a conserved domain of the Urotensin II peptide family [24,25]. In the zebrafish spinal cord, urp1 and urp2 are expressed in ventral CSF-cNs while other genes of the family are expressed in the caudal neurosecretory system [23,25,26].…”
Section: Upregulation Of Urp Signaling Participates In Scoliosis Onsementioning
confidence: 99%
“…Previous morphology and immunohistochemistry studies of the CNSS have found that CRH and UI were co-expressed (Cioni and Bordieri, 2003;Lu et al, 2004). Meanwhile, UI and UII could also be co-expressed in a fraction of Dahlgren cells (Parmentier et al, 2006). Therefore, the increased UI-positive cells might be recruited from the Dahlgren cells that expressed UII peptides.…”
Section: Discussionmentioning
confidence: 91%